The Use of Politeness Strategies in Online Teacher-Students’ Virtual Classroom Interaction - Hamdan Nuramdani (Universitas Negeri Semarang, 2023)
This research focused on analysing the politeness strategies in online teachers' and students' virtual classroom interaction at SMPN 16 Cirebon. Therefore, the main objective of this research was to explain the use of positive politeness strategies, negative politeness strategies, bald-on-record strategies, and off-record strategies and the relationship among the politeness strategies in teacher-students virtual classroom interaction in the online teaching-learning process at SMPN 16 Cirebon. The data were collected by using observation with recording and note-taking. The data was analyzed using thematic analysis, Braun and Clarke's theory. The finding showed that positive politeness, negative politeness, bald-on-record, and off-record strategies exist in virtual classroom interaction. The teachers used positive politeness to engage students' attention and build a comfortable situation in the online virtual classroom. At the same time, students used it to respect the teacher before conveying their questions or answering their opinions. The students and teachers use bald-on-record to communicate their feelings in an emergency. Students used off-record to avoid the teacher's questions, while the teacher used it to build the student's thoughts in the beginning activities. All the strategies correlate and impact creating an atmosphere or situation in online virtual classroom interaction.